2019
DOI: 10.1242/jeb.208595
|View full text |Cite
|
Sign up to set email alerts
|

Light avoidance by non-ocular photosensing system in the terrestrial slugLimax valentianus

Abstract: Although the eye is the best-studied photoreceptive organ in animals, the presence of non-ocular photosensing systems has been reported in numerous animal species. However, most of the roles that nonocular photosensory systems play remain elusive. We found that the terrestrial slug Limax valentianus avoids light and escapes into dark areas even if it is blinded by the removal of the bilateral superior tentacle. The escape behaviour was more evident for short-wavelength light. Illumination to the head with blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Unexpectedly, we noticed that the immunoreactivity (IR) of Gqrhodopsin was detected in the terminal of optic nerves if the brain was fixed within 24 h after tracer incorporation (Figure 3), which is probably due to the high expression level of Gq-rhodopsin (Matsuo et al, 2019;Nishiyama et al, 2019). Gq-rhodopsin-IR was only found in the medial lobe of the optic neuropile (white arrow in the upper panels of Figure 3).…”
Section: Optic Neuropile Bifurcates In Its Terminalmentioning
confidence: 92%
See 1 more Smart Citation
“…Unexpectedly, we noticed that the immunoreactivity (IR) of Gqrhodopsin was detected in the terminal of optic nerves if the brain was fixed within 24 h after tracer incorporation (Figure 3), which is probably due to the high expression level of Gq-rhodopsin (Matsuo et al, 2019;Nishiyama et al, 2019). Gq-rhodopsin-IR was only found in the medial lobe of the optic neuropile (white arrow in the upper panels of Figure 3).…”
Section: Optic Neuropile Bifurcates In Its Terminalmentioning
confidence: 92%
“…Slugs detect ambient light using not only their tentacular eyes but also their brain as a photosensor, although the possibility of dermal photosensing has also been proposed in the closely related pulmonate Lymnaea (Chono et al., 2002; Sunada et al., 2010). Thus, they can exhibit negative phototaxis behavior even if their bilateral eyes on the superior tentacle (ST) are removed (Nishiyama et al., 2019). We have previously demonstrated that the brain photoreceptors expressing Opsin5A (Opn5A), which constitutes a visual pigment, send projections to the contralateral optic neuropile through the cerebral commissure and form gap junctions between the terminals of retinal photoreceptors (Matsuo et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most slugs are omnivorous, nocturnal scavengers that feed on dead vegetation, fungi, dead animals, and other detritus (Barnes and Weil, 1945;Jennings and Barkham, 1975;Keller and Snell, 2002). While they possess simple eyes (and certain light sensitive areas of the brain) that can detect light intensity, they do not form clear images (Zieger et al, 2009;Nishiyama et al, 2019) and seek food using olfactory cues (Gelperin, 1974;Gelperin, 1975;Kiss, 2017). Where organisms are protected in more than one modality, it can be difficult to disentangle the contribution of each modality to defence; artificial light sources are an important tool in demonstrating a defensive role of light where chemical defences are also effective (Underwood et al, 1997;Marek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Field investigations revealed that slugs, including Arion lusitanicus , Deroceras reticulatum , and Arion distinctus , prefer to forage in dark conditions 16,17 . The light‐avoidance behavior of slugs makes their olfactory sense an indispensable sensory organ for locating food in dark conditions 16,18 . When slugs forage at night, volatiles released by plants can be perceived by slugs and help them discriminate host plants from non‐host plants, 19–22 therefore the volatiles from different plant species could be attractive or repellent.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The light-avoidance behavior of slugs makes their olfactory sense an indispensable sensory organ for locating food in dark conditions. 16,18 When slugs forage at night, volatiles released by plants can be perceived by slugs and help them discriminate host plants from non-host plants, [19][20][21][22] therefore the volatiles from different plant species could be attractive or repellent. Plant volatiles contain varied categories of chemicals, such as fatty acid derivatives, terpenes, phenylpropanoids, benzenoids, and so on.…”
Section: Introductionmentioning
confidence: 99%